Pre-Raphaelite Ornaments in the European Slaughterhouse: Pre-Raphaelitism and Croatian Culture - Jukić, Tatjana (Array, 2006)
The text traces the way in which Pre-Raphaelitism surfaces in Croatian cultural history as a trope of its construction.